1969
DOI: 10.1126/science.166.3910.1307
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Stimuli and the "Pseudo-Extinction" Effect

Abstract: Continuously rewarded rats show a decrease in running speed on a runway recently traversed by other rats undergoing experimental extinction. This "pseudo-extinction" effect is caused by discriminable odors emitted by extinction subjects. These odors could be confounding variables in studies using forms of aversive stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0
2

Year Published

1971
1971
1998
1998

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 7 publications
1
14
0
2
Order By: Relevance
“…A number of studies have demonstrated that odor can function as a cue for rats in spontaneous alternation (Douglas, 1966), maze learning (Means, Hardy, Gabriel, & Uphold, 1971;Wasserman & Jensen, 1969) and other types of tasks (Slotnick, 1974). In all of the above experiments, however, the salience of the odor was markedly increased either by combining odors from many rats all tested under the same condition or by having all odors except the stimulus odor removed or suppressed.…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies have demonstrated that odor can function as a cue for rats in spontaneous alternation (Douglas, 1966), maze learning (Means, Hardy, Gabriel, & Uphold, 1971;Wasserman & Jensen, 1969) and other types of tasks (Slotnick, 1974). In all of the above experiments, however, the salience of the odor was markedly increased either by combining odors from many rats all tested under the same condition or by having all odors except the stimulus odor removed or suppressed.…”
Section: Discussionmentioning
confidence: 96%
“…Ludvigson and others have postulated that this characteristic behavior pattern is determined by the discrimination of an odor associated with nonreward trials and covaries with an emotional response of frustration resulting from the absence of reward in an expected reward condition (CoUerain & Ludvigson, 1977;Howard & McHose, 1974;Pratt & Ludvigson, 1970;Wasserman & Jensen, 1969). Collerain and Ludvigson (1972) also found that this "nonreward" odor was avoided or escaped from by animals in a T -maze.…”
mentioning
confidence: 99%
“…Not only are these findings interesting with regard to their contribution to the general field of animal behavior, but are particularly important in view of the rat's extensive use in studies of learning and motivation, where such odor effects could confound experimentally manipulated variables. For example, the withholding of reinforcement from a rat that had been trained to run a straight alley produces an odor which results in an unconditioned decrement in the running speed of a subsequently tested animal (Wasserman and Jensen, 1969). The reinforcement and withholding of reinforcement from a predecessor have also been shown to be conditions producing odors which can serve as conditioned stimuli for discrimination using runways (Ludvigson and 1This research was done at…”
mentioning
confidence: 99%